2007
DOI: 10.4028/www.scientific.net/kem.330-332.637
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Bioactive Tantalum Metal via Anodic Oxidation Treatment

Abstract: After the Tantalum metal was subjected to the anodic oxidation at suitable voltage in 2M H2SO4 solution, tantalum oxide with rhombic or amorphous structure formed on the metal surface. The Oxide showed apatite formation ability in simulative body fluid at 6d. It meant the anodic oxidation treatment ia an effective method to accelerate the bioactivity of tantalum metal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Subsequent efforts were made to understand the rate controlling step and the movement/migration of metal ions during the anodic oxide growth on Ta. 90,103 For example, B. Verkerk et al 103 investigated the mechanism of tantalum oxide growth utilizing 3− and BO − throughout the outer layer. However, for tungstate, molybdate, chromate, and vanadate electrolytes, the incorporated impurities (W, Mo, Cr, and V) or anion species were suggested to be present only in the outermost layer, with the thickness too small to be determined by SIMS.…”
Section: Incorporation Of Species Frommentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequent efforts were made to understand the rate controlling step and the movement/migration of metal ions during the anodic oxide growth on Ta. 90,103 For example, B. Verkerk et al 103 investigated the mechanism of tantalum oxide growth utilizing 3− and BO − throughout the outer layer. However, for tungstate, molybdate, chromate, and vanadate electrolytes, the incorporated impurities (W, Mo, Cr, and V) or anion species were suggested to be present only in the outermost layer, with the thickness too small to be determined by SIMS.…”
Section: Incorporation Of Species Frommentioning
confidence: 99%
“…This study, for the first time, demonstrated the migration of metal ions through the oxide layer during its growth. Subsequent efforts were made to understand the rate controlling step and the movement/migration of metal ions during the anodic oxide growth on Ta. , For example, B. Verkerk et al investigated the mechanism of tantalum oxide growth utilizing radioactive labeling techniques. In 1972, E. Gunzel examined the anodization of Ta in electrolytes, such as chromic acid, phosphoric acid, sulfuric acid, and citric acid with variations in concentrations.…”
Section: Anodization Of Tantalummentioning
confidence: 99%
See 2 more Smart Citations
“…Anodic oxidation results in the formation of rough titanium oxide, which improves osseointegration. The oxidation process can be done in standard conditions as well as can be supported by spark-discharge process in the plasma electrolytic oxidation (PEO), done at high voltages [8][9][10]. As the results, formation of different size pores or cavities as well as nanotubes are possible [11][12][13].…”
Section: Introductionmentioning
confidence: 99%